Social network sites as learning environments and their implications for mental health - Hussenoeder, Felix S. (Frontiers in Digital Health, 2022)
Social network sites (SNSs) have become ubiquitous around the globe and interwoven with all aspects of life. In this article, I will argue that the communicative infrastructure of SNSs, i.e., all SNS-elements that allow users to communicate, is a key element for understanding their impact as it creates environments in which users, their behaviors, and social interactions are embedded. These digital environments facilitate and encourage fundamental mechanisms of implicit learning from feedback as well as observation in an unprecedented way. I will discuss how these technology-based learning environments impact the mental health of their users, e.g., by linking negative online feedback to depression and following influencers to disturbed eating. The article ends with a conclusion that emphasizes the advantages of understanding SNSs as environments in order to reflect the complexity, relevance, and ubiquitousness of the phenomenon.